ANALISIS MANAJEMEN PROMOSI UMKM PADA PROGRAM PODCAST SIKOPA DISKOMINFO KOTA PADANG - Heni Maryanti; Siti Fadilla (KINEMA: Jurnal Komunikasi dan Penyiaran, 2024)
This reseach the subject matter of this thesis is the management of the promotion of Micro, Small and Medium Enterprises contained in the Sikopa Podcast program of Diskominfo Padang City. The type of research used is qualitative research. The data collection techniques used are observation, interviews and document review. Data analysis techniques carried out, namely data reduction (summarizing, selecting key things, focusing when important, looking for themes and patterns), data presentation (brief description / chart / relationship between categories / flowchart / and the like) and conclusion drawing. Data validity assurance techniques used, namely source triangulation and technique/method triangulation. The results of this study concluded that, The form of Micro, Small and Medium Enterprises promotion carried out by the Sikopa Podcast program is to promote Micro, Small and Medium Enterprises in the form of video content and flyers that will be posted via Instagram. The promotional management activities carried out by the Sikopa Podcast are first, promotional planning activities on the Sikopa Podcast program, namely conducting briefings 2 days before the Sikopa Podcast program airs. Second, organizing activities on the Sikopa Podcast program by determining structures and positions and providing training to new members to gain knowledge when going into the field in carrying out the assigned tasks. Third, implementation activities on the Sikopa Podcast program promote not only on the Sikopa Podcast program because the product content itself and flyers will be made to inform the public. Fourth, supervision activities on the Sikopa Podcast program by evaluating the TPK about Micro, Small and Medium Enterprises products and carried out with several stages which will be reviewed by the coordinator.